AESTHETIC EXPERIENCES OF OUR EVERYDAY LIFE - Andra NEDELCU (Challenges of the Knowledge Society)
The everyday aesthetics represents a relatively new branch in the field of philosophy which brings into question the way some of our mundane habits, ordinary experiences and objects can be incorporated into the aesthetic area or can become a part of an aesthetic experience. While Yuriko Saito, author of “Everyday Aesthetics”, speaks about the Japanese tea ceremony as an aesthetic experience, while Paulina Rautio suggests hanging laundry as an aesthetic experience too. This paper attempts to make a quick review of the controversies related to the above mentioned subject matter and to bring forward some criteria upon which some of our everyday ordinary experiences, events or even objects can or cannot be translated as aesthetic. On what level can the acknowledgment of an ordinary experience be perceived as aesthetic and, thus, lead to the improvement of the quality of our life, is another aspect presented in this paper.